2017
DOI: 10.1002/cctc.201601678
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Ketone Hydrodeoxygenation for the Production of Fuels and Feedstocks from Biomass

Abstract: In this work, we describe a simple, heterogeneous catalytic system for the hydrodeoxygenation (HDO) of 5‐nonanone and 2,5‐hexanedione, which we use as model compounds for more complex biomass‐derived molecules. We present the stepwise reduction of ketones by using supported metal and solid acid catalysts to identify the intermediates en route to hydrocarbons. Although monoketone HDO can be achieved rapidly using moderate conditions (Ni/SiO2.Al2O3, HZSM‐5, 200 °C, 1.38 MPa H2, 1 h), quantitative γ‐polyketone HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…At 100 °C, the major product for both Ni and Co was 5-nonanol (72% and 79% selectivity, respectively). As the temperature increased to 150 °C, the major product changes to n-nonane as the rate of dehydration increases; this was found to be the temperature at which the rate of zeolite-catalyzed dehydration increases in batch reactions, 19 though nonanol is still present (18% for Ni-7/ZSM-5, 15% for Co-11/ZSM-5). With an increase of the temperature further to 200 °C, n-nonane remained the major product with slightly increased selectiv-itythe maximum n-nonane space time yields for both catalysts were achieved at this temperaturewhile the proportion of nonanol decreased (5% for Ni-7/ZSM-5, 3% for Co-11/ZSM-5).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At 100 °C, the major product for both Ni and Co was 5-nonanol (72% and 79% selectivity, respectively). As the temperature increased to 150 °C, the major product changes to n-nonane as the rate of dehydration increases; this was found to be the temperature at which the rate of zeolite-catalyzed dehydration increases in batch reactions, 19 though nonanol is still present (18% for Ni-7/ZSM-5, 15% for Co-11/ZSM-5). With an increase of the temperature further to 200 °C, n-nonane remained the major product with slightly increased selectiv-itythe maximum n-nonane space time yields for both catalysts were achieved at this temperaturewhile the proportion of nonanol decreased (5% for Ni-7/ZSM-5, 3% for Co-11/ZSM-5).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Our initial experiments were a direct translation of the batch reactions. 19 In an attempt to reduce 5-nonanone to 5-nonanol we used Ni/SiO 2 −Al 2 O 3 at 200 °C, 1.38 MPa H 2 with a residence time of 60 min. However, under these conditions in the flow reactor, we observed complete HDO to n-nonane rather than a replication of the conversion to the alcohol as observed in the batch reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Residual starting material was easily recovered, and when reused, allowed for a quantitative yield. Hydrodeoxygenation with Ni/Al 2 O 3 À SiO 2 (20 wt %) and NbOPO 4 (50 wt %) [296,297] under optimized conditions (180°C, 1.38 MPa H 2 , 16 h) gave a saturated alkane mixture in 83 % isolated yield. The major product (91.2 %) was the cyclobutane isomer with 8.8 % of the ring-opened species and its corresponding isomers (Scheme 32).…”
Section: Photochemical [2 + 2]-cycloadditionmentioning
confidence: 99%
“…Although ketones can be hydrogenated to their corresponding alcohol, a kinetic HDO study in the literature showed that the rate of ketone formation is three orders of magnitude greater than the rate of its consumption [45]. Studies made with noble metals [48,49] indicated that Pd and Pt were active in converting ketone to their corresponding hydrocarbon, but Rh and Ru were not active in hydrogenating the ketone group. Ketones are inadequate for fuel blends due to their ability to degrade plastics and rubber, and due to their possible instability [47].…”
Section: Characterization Of Spent Catalystsmentioning
confidence: 99%